On the cause of low thermal stability of ethyl halodiazoacetates - Mortén, Magnus; Hennum, Martin; Bonge-Hansen, Tore (Beilstein Journal of Organic Chemistry, 2016)
Rates for the thermal decomposition of ethyl halodiazoacetates (halo = Cl, Br, I) have been obtained, and reported herein are their half-lives. The experimental results are supported by DFT calculations, and we provide a possible explanation for the reduced thermal stability of ethyl halodiazoacetates compared to ethyl diazoacetate and for the relative decomposition rates between the chloro, bromo and iodo analogs. We have also briefly studied the thermal, non-catalytic cyclopropanation of styrenes and compared the results to the analogous Rh(II)-catalyzed reactions.
Keywords: carbenes; catalysis; cyclopropanation; halo diazoacetates; half-lives; thermal stability